The written production of argumentative and dissertation text: a didactic project based on Bakhtin's philosophy - Marcos Rogério Martins Costa; Patricia Margarida Farias Coelho; Irene Garcia Medina (Universidade Estadual de Campinas, 2018)
This article is characterized as a theoretical and practical research related to a project developed during the year 2015 in two schools - one public, the other private- , in the city of Birigui, State of São Paulo, Brazil. The main goal of the study was to analyze: the pedagogical project and the teachers' activities oriented towards teaching and learning of argumentative and dissertation texts. The methodology used in this research comprised: (i) visiting both schools, (ii) producing a description of ongoing school practices, with focus on the teaching of argumentative and dissertation texts, (iii) suggesting a teacher's activity to improve this apprenticeship, (iv) putting this activity into practice and (v) analyzing obtained results. The theoretical framework used for this study was the Bakhtinian philosophy (BAKHTIN, 2013; 2006a; 2006b; 2006c; 2006d; 2010; 2013; VOLOSHINOV, 1986). This theoretical approach was chosen due to the importance of comprehension of the text not just as an amalgamated set of words, phrases and paragraphs; other than that, we understand it as a structure of meaning, in which we encounter linguistic forms, ideologies and discursive stance. At last, we can say the results show that the argumentative texts render assistance to the development of the students' argumentative competence and skill, that is, in their ability to argue and organize ideas in a communicative situation.